Professional and Personal Profile of a School Special Educator in the Conditions of a Primary School in the Czech Republic - Stárek, Lukáš; Klugerová, Jarmila; Daněk, Alois; Vlach, František (Cadernos de Educação Tecnologia e Sociedade, 2024)
The article deals with the professional image of the school special educator in the environment of primary schools in the Czech Republic. It focuses on his/her role, workload, cooperation with other institutions and importance in the context of inclusive education. The text describes historical changes in the perception and inclusion of pupils with special educational needs, including current legislative and practical approaches in the field of education. The aim of the article is to provide insight into the day-to-day challenges, workload management strategies and perceptions of the professional role of the school special educator within the educational process.